Marketing Channel and Marketing Margin of Coconut Palm Sugar Srikandi in the Srikandi Women’s Cooperative Purworejo, Central Java - Nurlaila Fatmawati; Aulia Rahmawati (SEAS (Sustainable Environment Agricultural Science), 2021)
Coconut palm sugar Srikandi is different from other sugar. Coconut palm sugar Srikandi is derived from the raw material of nira obtained from coconut trees that grow on organic certification land. This organic certificate was issued by the Dutch Control Union, namely the EU Organic Farming certificate and USDA Organic certificate from America. In addition, there was already a halal label from LPPOM Central Java Province and PIRT Purworejo Regency Health Office. Coconut palm sugar Srikandi could reach the market in accordance with organic certificates that were Europe, America, Australia and Sri Lanka. This study aims to identify the marketing channels, marketing margins, farmer's share and the analysis of profit-to-cost ratios. The type of research used by the survey method. The research location was chosen by probability sampling method, that was in Loano District and Kaligesing District, Purworejo Regency as an object and coconut palm sugar tapper who is a member of Srikandi Women's Cooperative as the subject. The most efficient marketing channel research resulted with a marketing margin value of Rp. 15.000 / kg, farmer's share value of 53.13% and the value of profit and cost ratio of 9.78 are found on the channel III.